Universiti Teknologi MARA Pahang forest reserve: forest park in the campus - Hashim, Sarina; Mustaffa, Muzamil; Kasim, Jamaludin (Universiti Teknologi MARA, 2009)
The campus management of Universiti Teknologi MARA (UiTM) Pahang has chosen 'Kampus Khazanah Alam' (Natural Heritage Campus) as its tagline. To support the management in identifying and recognising its natural heritage, a group of researchers from UiTM Pahang, UiTM Shah Alam and UiTM Perak held a joint exploration into UiTM Pahang Forest Reserve from 25th to 27th October 2008 to record its unique biodiversity. The three day event in the dipterocarp lowland forest was a stint in the natures' wonderland. The exploration declares UiTM Pahang Forest Reserve as a forest park in the campus. This project is considered an important step towards flora and fauna preservation and conservation. However, the effort must be followed up with commitment and sustainable master plans focusing on preserving our precious diversity